INOVASI PEMBELAJARAN DI ERA DIGITAL: MEMPERKUAT KOMPETENSI GURU MELALUI GEMINI ARTIFICIAL INTELLIGENCE (AI) - Burhan, Burhan; SAS, Abdillah; Rizal, A; Muhammad, Achmad Fajar; Januarty, Restu; Rampeng, Rampeng (LPPM Universitas Islam 45 Bekasi, 2025)
Gemini AI-based learning design training at SD Inpres Monginsidi Makassar City aims to improve teachers' competence in utilising artificial intelligence (AI) technology to create more innovative, adaptive, and effective learning. The training was attended by 30 teachers who were given materials on the introduction of Gemini AI, how to use the platform to design learning that suits students' needs, as well as hands-on practice in designing and implementing technology-based lesson plans. The Gemini AI-based learning design training at SD Inpres Monginsidi used a participatory and collaborative approach. The training method also applied in the service programme consists of several stages designed to maximise teachers' understanding and skills in using Gemini AI technology. The results of the training showed an increase in teachers' ability to design digital learning that is more interactive and personalised. Despite challenges in terms of infrastructure and mental readiness, the training succeeded in expanding teachers' understanding of artificial intelligence technology and its use in education. Thus, the results of this training contribute significantly to strengthening teachers' competencies and improving the quality of learning in primary schools.